Relations of muscle strength and body mass when performing different vertical jumps - Kukric, Aleksandar; Joksimovic, Marko; Petrovic, Borko; Zlojutro, Nemanja; Dobras, Radenko (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Sports result largely depends on body dimensions and the development of motor skills. Aim of Study. The aim of the study was to examine the relationship between body mass and muscle strength test results when performing different variants of vertical jumps. Material and Methods. Sixty selected senior basketball players participated in the study. According to the criterion of the position played in the team, the respondents were divided into two groups. One group consisted of external players (n = 30), while the other group comprised internal players (n = 30). Results. In both groups of subjects, low correlation coefficients were obtained between body weight and results of indirect muscle strength assessment tests (0.00; –0.05; –0.00; –0.02), as well as weak correlation coefficients between results of direct muscle strength assessment tests and body weight (0.44; 0.36; 0.41; 0.38). In the group of external players in the tests for the direct assessment of muscle strength allometric exponents b = 0.82 and b = 0.74 were recorded, while for internal players in these tests allometric exponents b = 0.73 and b = 0.72 were obtained. Tests for the indirect assessment of muscle strength in the group of external players gave allometric exponents b = 0.09 and b = –0.00, while in the group of internal players the exponents were b = –0.10 and b = –0.25. Conclusions. This study showed that the results in the tests for the direct assessment of muscle strength when performing fast movements are dependent on body mass, while those in tests for the indirect assessment of muscle strength when performing fast movements do not depend on body mass.
Keywords: basketball players; body dimensions; allometric; scaling; fast movements